Variasi Fonologi dan Leksikon Dialek Melayu Sambas Desa Tengguli, Mekar Jaya, dan Sekura, Kabupaten Sambas - Fariza, Fariza; Patriantoro, Patriantoro; Seli, Sesilia (Universitas Islam Sumatera Utara, 2025)
This study aims to examine the phonological and lexical variations of the Malay Sambas dialect spoken in the villages of Tengguli, Mekar Jaya, and Sekura, located in Sambas Regency. The research employs a descriptive qualitative method to analyze linguistic differences based on data collected from native Malay speakers residing in the three villages. The data consist of basic Swadesh vocabulary and spoken sentences that reflect the phonological and lexical characteristics of the local dialect. The findings reveal the presence of 31 lexical variations and 10 phonological variations among the three villages. These variations are influenced by geographical, demographic, and historical factors, which contribute to the linguistic diversity of the Malay Sambas dialect. Furthermore, the study highlights the pedagogical implications of these findings for the development of a Semester Learning Plan (Rencana Pembelajaran Semester, RPS) in teaching phonological and lexical variation within local language education.